Seasonal trends in brood sex ratio reflect changes in early-life physiological condition of chicks in the whiskered tern. Issue 4 (1st October 2016) - Minias, Piotr
Abstract : When fitness return differs for sons and daughters, parents are selected to adjust brood sex ratio to maximise the reproductive value of their offspring. The aim of this study was to investigate seasonal adjustments in brood sex ratio of a sexually dimorphic colonial larid, the whiskered tern Chlidonias hybrida . I found a significant seasonal change in brood sex ratio from sons to daughters in the studied whiskered tern population. This pattern was consistent with a seasonal decline in the early-life physiological condition of both male and female whiskered tern hatchlings measured with blood concentrations of haemoglobin. The incapability of late breeders to raise male offspring of high quality indicates that they should adaptively adjust brood sex ratio towards daughters, which are more likely to reproduce regardless of their phenotypic and genetic quality. Thus, I suggest that the seasonal change in brood sex ratio from sons to daughters in the whiskered tern may be attributed to the declining quality of male progeny produced over the course of the breeding season, although this trend may be non-exclusively reinforced by size-related differences in the costs of rearing male and female offspring.